2022
DOI: 10.3389/fpls.2022.889045
|View full text |Cite
|
Sign up to set email alerts
|

How Strigolactone Shapes Shoot Architecture

Abstract: Despite its central role in the control of plant architecture, strigolactone has been recognized as a phytohormone only 15 years ago. Together with auxin, it regulates shoot branching in response to genetically encoded programs, as well as environmental cues. A central determinant of shoot architecture is apical dominance, i.e., the tendency of the main shoot apex to inhibit the outgrowth of axillary buds. Hence, the execution of apical dominance requires long-distance communication between the shoot apex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 161 publications
(273 reference statements)
0
6
0
Order By: Relevance
“…Thus, increased fructose mobilization by high expression of SWEET17 , as occurring under drought, leads to suppression of BRC1 and MAX2 , which in sum stimulates branching. Because MAX2 expression and signaling are directly influenced by factors such as strigolactone concentration (Chevalier et al, 2014; Khuvung et al, 2022) it is not surprising that observed MAX2 expression differences between wild types and sweet17 mutants are not significant (Figure 5 B). Anyhow MAX2 expression supports the observed BRC1 regulation and branching differences between wild types and sweet17 mutants (Figure 4 and Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased fructose mobilization by high expression of SWEET17 , as occurring under drought, leads to suppression of BRC1 and MAX2 , which in sum stimulates branching. Because MAX2 expression and signaling are directly influenced by factors such as strigolactone concentration (Chevalier et al, 2014; Khuvung et al, 2022) it is not surprising that observed MAX2 expression differences between wild types and sweet17 mutants are not significant (Figure 5 B). Anyhow MAX2 expression supports the observed BRC1 regulation and branching differences between wild types and sweet17 mutants (Figure 4 and Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…Strigolactone can also stimulate shoot elongation by modulating auxin transport, leading to increased plant height with higher concentrations of strigolactone causing more significant height increments [38]. Moreover, they enhance dry weight and root development via better nutrient uptake and increased biomass production [39]. Furthermore, strigolactone promotes branching by inhibiting the outgrowth of axillary buds, increasing the number of primary branches, a desirable trait in agriculture for potential fruit production [40].…”
Section: Morphological Attributesmentioning
confidence: 99%
“…SL-biosynthesis takes place mainly in the root [ 100 ] and secondarily in the stem [ 101 ]. They are produced at extremely low concentrations by an isomerase (D27) and two carotenoid cleavage dioxygenases (CCDs), i.e., CCD7/MAX3 and CCD8/MAX4, which convert β-carotene to carlactone.…”
Section: Strigolactones Are Involved In the Regulation Of Lateral And...mentioning
confidence: 99%